2 d x 2 d 2 y + 3 d x d y + y = e − 3 x , x ∈ R
Let y : R → R be a solution of the above ordinary differential equation, satisfying x → ∞ lim e x y ( x ) = 0 . Find y ( 0 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Well explained.... Thanks (+1)
One possible solution is:
y ( x ) = c e − 3 x
Plugging this into the equation:
1 8 c e − 3 x − 9 c e − 3 x + c e − 3 x = e − 3 x
1 0 c e − 3 x = e − 3 x
1 0 c = 1
c = 0 . 1
y ( x ) = 0 . 1 e − 3 x
So:
y ( 0 ) = 0 . 1
Yes, the particular solution y p = c e − 3 x ends up being all we need to consider. The homogenous solution is y h = a e − x / 2 + b e − x , and so the general solution is
y = y h + y p = a e − x / 2 + b e − x + c e − 3 x , and so
x → ∞ lim e x y = x → ∞ lim ( a e x / 2 + b + c e − 2 x ) = 0 only if a = b = 0 .
Problem Loading...
Note Loading...
Set Loading...
The characteristic equation of the ordinary differential equation is:
2 D 2 + 3 D + 1 ( 2 D + 1 ) ( D + 1 ) ⟹ D = 0 = 0 = − 2 1 , − 1
Therefore, the general solution of the ODE is y ( x ) = c 1 e − 2 x + c 2 e − x .
Assuming the particular solution of the ODE be:
y ( x ) y ′ ( x ) y ′ ′ ( x ) ⟹ 2 y ′ ′ ( x ) + 3 y ′ ( x ) + 1 2 y ′ ′ ( 0 ) + 3 y ′ ( 0 ) + 1 ⟹ c = c e − 3 x = − 3 c e − 3 x = 9 c e − 3 x = 1 0 c e − 3 x = 1 0 c = 1 = 1 0 1
Therefore, the particular solution of the ODE is y ( x ) = 1 0 e − 3 x .
And the complete solution of the ODE is:
y ( x ) ⟹ e x y ( x ) ⟹ c 1 ⟹ y ( x ) ⟹ y ( 0 ) = c 1 e − 2 x + c 2 e − x + 1 0 e − 3 x = c 1 e 2 x + c 2 + 1 0 e − 2 x = c 2 = 0 = 1 0 e − 3 x = 1 0 1 = 0 . 1 Since x → ∞ lim e x y ( x ) = 0